Planta industrial de extrusión: beneficios para mitigar parte de las problemáticas ambientales y de desempleo en la ciudad de Neiva (2021)
This document shows the proposal and a specific architectural design of a Plastic Extruder Industrial plant in the department of Huila, specifically in the Neiva free zone. First, a collection and general description of the relevant information for the development of the project is carried out. Next, a model of great utility from the practical point of view is proposed, which relates the problems that the municipality is going through, and how it is intended to provide solutions that help mitigate part of the unemployment problems with environmental contribution in the city of Neiva.